PENGGUNAAN PROTOTYPING DALAM PEMBUATAN APLIKASI MOBILE UNTUK LATIHAN TES TERTULIS IZIN MENGEMUDI - Irman Effendy; Nyimas Sopiah (Jurnal Ilmiah Matrik, 2017)
Mobile technology is a technology that is growing very rapidly. The use of mobile phones are not a luxury anymore, but the items that are needed in everyday life. Prospective drivers sometimes do not understand the material written exam they will do to get a driver's license. This is what causes the failure in the written exam, a candidate's knowledge because the driver did not understand the details of the traffic rules that have been used. To anticipate this, the authors are interested in creating a training application written exam to get a driver's license by using a mobile device. Software development method used is prototyping methods.